Lesson Study for Learning Community to Support Creative Teachers in Designing Quality Learning: Lesson Study Practices on Bawean Island, Gresik Regency - Nur Fauziyah; Ulfatul Ma’rifah; Slamet Asari; Churun L. Maknun (Kontribusia : Research Dissemination for Community Development, 2021)
This study aims to describe the implementation of LSLC (Lesson Study for Learning Community) which was carried out on a remote island. The subjects in this study were 29 teachers of MTs (Madrasah Tsanawiyah) and MA (Madrasah Aliyah) Penaber on the island of Bawean Gresik. To find out the impact of LSLC on increasing teacher creativity in developing quality learning tools, an LSLC product analysis was carried out in the form of chapters and lesson designs. Quantitative data from the pre-test and post-test results are also used as a comparison of the impact of increasing teacher understanding of the LSLC principle. Based on this study, it was found that LSLC activities were able to increase teacher creativity in designing quality learning. Learning that focuses on efforts to solve student problems in learning. Learning that emphasizes how learning can grow students' abilities in critical thinking, creative, collaborative and communication. During the implementation of LSLC, it also has an impact on increasing the positive attitude of teachers as well as communication and collaboration skills. The quantitative data analysis also shows that during the implementation of the LSLC there is an influence on the teacher's understanding of the LSLC principles.